The Arecibo Observatory as an MST radar - Woodman Pollitt, Ronald Francisco (1983)
The present paper will make a brief description of the four radars available at the Observatory. We have included in the bibliography a list of references where more detailed descriptions of these systems can be found. The list also includes papers of scientific nature which further illustrate the capabilities of the Arecibo Obeervatory asan MST radar. We will not cover the capabilities of the observatory for mesospheric research using incoherent scatter techniques. These capabilities have been recently reviewed by MATHEWS [1981, 1984].